2018
DOI: 10.1080/09243453.2018.1484776
|View full text |Cite
|
Sign up to set email alerts
|

The effect of schools on school leavers’ university participation

Abstract: This paper considers the role that schools have in determining whether school leavers participate in higher education or not. It examines the association between schools and university participation using a unique dataset of 3 cohorts of all young people leaving maintained schools in Wales. School "effects" are identified, even after controlling for individual-level factors, such as their prior attainment, socioeconomic circumstances, ethnicity, and special educational needs. Schools appear to have a particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Deming and colleagues (2014) study students in Charlotte, North Carolina and find that one's high school matters in determining whether one actually participates in postsecondary education. Research using national samples in the U.S. (Altonji & Mansfield, 2011;Rumberger & Palardy, 2005), national data in Wales (Taylor et al, 2018), and statewide databases in the U.S. (Jennings et al, 2015) has found variation across schools of similar magnitude. Jennings and colleagues (2015) go further to argue that the variance in school effects is larger for baccalaureate college attendance than for exam scores.…”
Section: School Effects Research: Canon and Recent Advancesmentioning
confidence: 99%
“…Deming and colleagues (2014) study students in Charlotte, North Carolina and find that one's high school matters in determining whether one actually participates in postsecondary education. Research using national samples in the U.S. (Altonji & Mansfield, 2011;Rumberger & Palardy, 2005), national data in Wales (Taylor et al, 2018), and statewide databases in the U.S. (Jennings et al, 2015) has found variation across schools of similar magnitude. Jennings and colleagues (2015) go further to argue that the variance in school effects is larger for baccalaureate college attendance than for exam scores.…”
Section: School Effects Research: Canon and Recent Advancesmentioning
confidence: 99%
“…The influence which secondary schools have on students' entry to higher education has attracted research interest in recent years, although our knowledge of it is less extensive than the abundant evidence relating to students' individual characteristics such as attainment, sex or socio-economic status (Taylor et al 2018;Donnelly 2015). The question is whether schools are influential over and above their effects through attainment.…”
Section: Contextmentioning
confidence: 99%
“…Some of this research has distinguished among different categories of higher education. Closest to the classification which is used in the present paper is that by Taylor et al (2018), who studied entry not only to degree courses at any university but also to shorter (usually two-year) courses or to degree courses in the highest-status universities. The distinction between degrees and two-year diplomas is analogous to that between four-year and twoyear programmes in the USA, school effects on entry to which were investigated by Palardy (2015).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the knowledge and support required to access elite universities appears unevenly distributed and where schools are more effective at increasing participation, their effect is not uniform. Rather, some schools are better at improving the likelihood of accessing elite universities for females and others for males (Taylor et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%